Efektifitas Implementasi Peraturan Bupati Pasaman Barat Nomor 47 Tahun 2022 Tentang Penataan Wilayah Kejorongan Di Kecamatan Kinali Kabupaten Pasaman Barat - Helti Handraini; Aldri Frinaldi (Hakim, 2024)
This research aims to evaluate the effectiveness of the implementation of West Pasaman Regent Regulation Number 47 of 2022 concerning Arrangement of the Kejorongan Area in Kinali District, West Pasaman Regency. The research method used is qualitative with a descriptive approach. The objectives of this research include providing a description, recording, analysis and interpretation of the conditions for implementing these regulations. Data was collected through observation, interviews and documentation studies, with the validity of the data tested using the triangulation method. The research results show that the implementation of this regulation still faces a number of challenges, including a lack of outreach to the community and their involvement in the decision-making process. The resources involved, both in terms of human resources and finance, are also still an obstacle. Bureaucratic attitudes and organizational structures need to be strengthened to ensure sustainable policy implementation. The conclusion of this research is that to increase the effectiveness of implementing West Pasaman Regent Regulation Number 47 of 2022, improvements need to be made in terms of socialization, community involvement, as well as increasing resources and bureaucratic readiness. It is hoped that the implications of this research can provide constructive input for related parties in improving the quality of implementation of policies for structuring the Jorongan area in this area.